Uporaba izrazno-ustvarjalnih medijev v socialnem delu in sorodnih poklicih pomoči - Kustec, Klavdija (Socialno delo, 2017)
The article presents some results of the study on the use of expressive and creative media in social work and the related helping professions in Slovenia. The term expressive and creative medium comprises drawing, painting, movement-dance, puppetry, theatre-drama, creative writing and reading, photography, video art and similar, and tries to answer the question of how to use these media creatively, when offering support and help. According to the results of the qualitative study, expert workers in the field of support and help have, on average, applied expressive and creative approaches for between five to ten years. They report noticing many positive aspects of the use of these media in their work with participants. However, they also observe certain risk factors in this kind of work. The method of work that the expert workers use in their work with expressive and creative media is group work, followed by work with individuals. The study showed that additional expert training of social workers in the related helping professions would be needed when using expressive and creative media in social work.
Keywords: ustvarjalnost; umetnost; art; terapija; therapy; socialo delo; poklici pomoči; uporabniki; tveganje